2001
DOI: 10.1021/tx010137i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Potential Toxic Metabolites of Tamoxifen Analogues:  Droloxifene and Toremifene o-Quinones

Abstract: Tamoxifen remains the endocrine therapy of choice in the treatment of all stages of hormone-dependent breast cancer. However, tamoxifen has been shown to increase the risk of endometrial cancer which has stimulated research for new effective antiestrogens, such as droloxifene and toremifene. In this study, the potential for these compounds to cause cytotoxic effects was investigated. One potential cytotoxic mechanism could involve metabolism of droloxifene and toremifene to catechols, followed by oxidation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…The same metabolic profile has been observed with toremifene (39, see Fig. 4) and droloxifene (40), for which adducts between their respective QMs with GSH and deoxynucleosides have been detected in vitro [22].…”
Section: Examples Of Qms That Are Anticancer Compoundssupporting
confidence: 77%
See 1 more Smart Citation
“…The same metabolic profile has been observed with toremifene (39, see Fig. 4) and droloxifene (40), for which adducts between their respective QMs with GSH and deoxynucleosides have been detected in vitro [22].…”
Section: Examples Of Qms That Are Anticancer Compoundssupporting
confidence: 77%
“…However, it has limited bioavailability and poor pharmacokinetics. A lipophilic derivative of ECG, TMECG (22), has been designed to improve its pharmacological characteristics [29]. This transformation led to a stronger antitumor compound but only on melanoma cells.…”
Section: Examples Of Qms That Are Anticancer Compoundsmentioning
confidence: 99%
“…However this non-genomic effect (i.e. an effect not mediated by a direct interaction with DNA) is observed only at high concentrations [10]. To date, the molecular targets and mechanism of action of OH-TAM in breast cancer cells are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising, because Fan et al, 2000 have shown that 1,8-Michael or 1,6-Michael addition of GSH to the quinone methide is a reversible process and that the adduct has a short half-life. In addition, 4-hydroxytamoxifen has been shown to form adducts with deoxynucleosides (Yao et al, 2001), and Notley et al (2002) have shown that recombinant P450s 2B6 and 2C19 catalyzed drug-protein adduct formation through 4OHtam and not catechol formation, whereas P450s 2D6 and 3A5 generated catechol metabolite formation and not drug-protein adduct formation. We were able to successfully identify and characterize a P450 adduct using recombinant purified CYP2B6.…”
Section: Discussionmentioning
confidence: 99%